Glimt fra Elie Wiesels forfatterskap - Høst Heyerdahl, Gerd (Nordisk judaistik/Scandinavian Jewish Studies, 1988)
In this article, the author reflects on the life and writings of Elie Wiesel. His works, which are to a great extent of fictional character, bear influences from his own life, existential questions, Jewish history and fate. This article provides an overview of Wiesel’s works and tries to find connections throughout his works.